2009
DOI: 10.1016/j.ijid.2008.11.027
|View full text |Cite
|
Sign up to set email alerts
|

First-line anti-tuberculosis drug resistance patterns and trends at the national TB referral center in Iran—eight years of surveillance

Abstract: There has been an increasing trend in drug resistance in recent years, particularly in retreatment cases. Hence, revision of the national TB control program, reevaluation of the role of the World Health Organization category II (CAT II) regimen, as well as the conducting of a nationwide drug resistance survey, are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 16 publications
(18 reference statements)
9
45
3
1
Order By: Relevance
“…16 times less than that among Afghans (22). Afghan patients include more than half of the multidrug-resistant tuberculosis cases in Iran, which reflects insufficient health services and surveillance infrastructure in their country (23). In a survey conducted by Farnia et al the rate of reactivation versus recent transmission was evaluated among Afghan and Iranian relapse cases and the impact of Afghan immigrants on the national tuberculosis control program of Iran due to intracommunity transmission between Afghan and Iranian tuberculosis cases was highlighted (24).…”
Section: Immigrantsmentioning
confidence: 99%
See 4 more Smart Citations
“…16 times less than that among Afghans (22). Afghan patients include more than half of the multidrug-resistant tuberculosis cases in Iran, which reflects insufficient health services and surveillance infrastructure in their country (23). In a survey conducted by Farnia et al the rate of reactivation versus recent transmission was evaluated among Afghan and Iranian relapse cases and the impact of Afghan immigrants on the national tuberculosis control program of Iran due to intracommunity transmission between Afghan and Iranian tuberculosis cases was highlighted (24).…”
Section: Immigrantsmentioning
confidence: 99%
“…It has also been demonstrated that the patients infected with rifampicin resistant strains will encounter a higher failure rate with short-course 6-month chemotherapy (32). These patients require treatment for at least two years while the treatment is 70 times more costly accompanied by much higher mortality rate (about 40% -60%) (23). In different parts of the world, multiple types of mutations have been identified in rifampicin-resistant M. tuberculosis clinical isolates, most of which are 10 codon point mutations, while only a few isolates have insertion or deletion.…”
Section: Treatment Policy and Antibiotic Resistancementioning
confidence: 99%
See 3 more Smart Citations